Skin and bones : and other Mike Bowditch short stories - Doiron, Paul (Doiron, Paul. Mike Bowditch mysteries., 2025)
"For the first time in print, Skin and Bones features a collection of eight gripping original short stories in the bestselling Mike Bowditch series--including one brand new, never-before-published story--from Edgar-award nominated author Paul Doiron. In THE BEAR TRAP, legendary Maine woodsman and bush pilot Charley Stevens tries to convince young Mike of the dangers awaiting rookie game wardens. RABID draws Mike into the story of a gruesome case involving a bat with rabies from his Charley Steven's past (2019 Edgar award nominee for Best Short Story). When a visiting hunter goes missing in the middle of a snowstorm, a young Charley Stevens sets off to rescue him-but begins to suspect the man may not want to be found in BACKTRACK. In THE IMPOSTER, Mike is confronted with a baffling case of stolen identity when he discovers a dead body whose driver's license claims he is none other than Mike Bowditch himself. Mike tracks down a sinister prowler who turns a couple's dream vacation home into a nightmare in THE CARETAKER. An investigation into the killing of a bald eagle in SKIN AND BONES unearths an old case of a missing young man whose physically abusive brother might have murdered him. In SNAKEBIT, Mike must hunt down a killer who uses the unlikeliest of murder weapons: rattlesnakes. (Brand New!) "--